Understanding the impact of a new approach to the safeguarding of children at risk: an evaluation protocol - Buivydaite, R; Tsiachristas, A; Thomas, S; Farncombe, H; Perera-Salazar, R; Fitzpatrick, R; Vincent, C (Ubiquity Press, 2022)
Introduction: Child Safeguarding Services intervene in situations where a child is at risk of serious emotional or physical harm. The response will vary according to the level of risk, but in serious cases, a child may need to be removed from danger and cared for by foster parents either temporarily or permanently. The number of children being taken into care has increased markedly in recent years in the United Kingdom. Oxfordshire County Council (OCC) is implementing a new approach to the welfare of children (Family Solutions Plus; FSP) in which the focus is to support the whole family and ideally reduce the need for foster care. In this paper, we describe a proposed programme of evaluation to examine the impact of FSP on the time children are in contact with services, the nature of the support provided, experience of children and families, the experience of staff, and longer term outcomes for children, particularly whether they remain within the family or need to be cared for outside the home. Methods and analysis: A mixed methods approach will be taken in an observational retrospective study of children’s social care services. Quantitative research will include descriptive analysis on data routinely collected by OCC, examining the effect on time spent in services, outcomes for children and how these outcomes are mediated by family characteristics and circumstances. Qualitative research will be carried out using individual interviews and focus groups with children, families and staff in the teams providing family safeguarding services to capture their experiences with the new model. Ethics and dissemination: This project has been registered with the OCC as a service evaluation. The qualitative studies will seek ethical approval from Oxford University Ethics Committee. A local data sharing agreement will govern the transfer of quantitative data. Results will be disseminated through newsletters, community forums, professional publications and conference presentations to national and international audiences.